СУЧАСНІ ПІДХОДИ ДО ВИЗНАЧЕННЯ ПОНЯТТЯ, МІСТУ І СТРУКТУРИ ЕКОЛОГІЧНОЇ КУЛЬТУРИ МАЙБУТНЬОГО ВЧИТЕЛЯ (Педагогіка вищої та середньої школи, 2004)
The different approaches for the definition of the essence, of the notion of ecological culture, are analyzed. Great attention is focused on the structural components of the ecological culture of future teachers.